Economic growth and macroeconomic dynamics : recent developments in economic theory - Dowrick, Steve; Pitchford, Rohan; Turnovsky, Stephen J. (Cambridge University Press, 2004)
The development of the endogenous growth model rekindled interest in growth theory. In contrast to the neo-classical model, long-run endogenous growth emerged as an equilibrium outcome, reflecting the behaviour of optimizing agents in the economy. This book brings together a number of contributions in growth theory and macroeconomic dynamics, reflecting these developments and the ongoing debate over the relative merits of neo-classical and endogenous growth models. It focuses on the emergence of three important aspects: First, it develops growth models that extend the underlying theory in different directions. Second, it addresses one of the concerns of the literature on growth and dynamics: the statistical properties of underlying data and the effort to ensure that growth models are consistent with empirical evidence. Third, it discusses the increasingly international focus of macrodynamics and growth theory, an inevitable consequence of the integration of the world economy.